Effect of theanine and polyphenols enriched fractions from decaffeinated tea dust on the formation of Maillard reaction products and sensory attributes of breads. (15th April 2016) - Culetu, Alina; Fernandez-Gomez, Beatriz; Ullate, Monica; del Castillo, Maria Dolores; Andlauer, Wilfried
Highlights: Theanine and polyphenols enriched fractions (TEF and PEF) from tea dust were studied. PEF and TEF inhibited fluorescent AGEs formation in glycoxidation model systems. Extent of Maillard reaction in the enriched breads was analyzed. PEF lower the level of fluorescent AGEs formed during baking. The best bread formulation from nutritional and sensorial aspects was with 30% PEF. Abstract: The antiglycoxidative properties of theanine (TEF) and polyphenols enriched fractions (PEF) prepared from tea dust were tested in a model system composed of bovine serum albumin (BSA) and methylglyoxal (MGO). PEF caused a decrease in available free amino groups of BSA in presence and absence of MGO, suggesting the simultaneous occurrence of glycoxidation reaction and phenols-protein interaction. The presence of PEF and TEF inhibited formation of fluorescent advanced glycation end-products (AGEs). Moreover, theanine (TB) and polyphenol-enriched bread (PB) were formulated. A significant increase in free amino groups was observed in TBs with a dose–response effect, while addition of PEF in bread produced a significant decrease ( p  < 0.05). PEF efficiently reduced fluorescent AGE formation in breads compared with TEF. The results are in line with the simplified model systems. PEF used as food ingredient allows obtaining a tasty food possessing health promoting properties and lower content of potential harmful compounds (AGEs).